DIOPHANTINE EQUATIONS AND THEIR APPLICATIONS - Conceição de Almeida, Dione; Cristina Barros Pedroza, Ivone (Journal of Interdisciplinary Debates, 2024)
This work addressed Diophantine equations as a solution method using mathematical researchers who explore the theme using problem situations that can be found in everyday life. In this way, the relevance of mathematics is highlighted and it is emphasized that imagination and abstraction are indispensable resources for understanding it. Finally, the need to study the methodology used in solving problems by the teacher in the classroom is highlighted, as the method contributes to the process of acquiring knowledge.